2009
DOI: 10.1245/s10434-009-0648-5
|View full text |Cite
|
Sign up to set email alerts
|

IMP3 Is a Novel Prognostic Marker that Correlates with Colon Cancer Progression and Pathogenesis

Abstract: IMP3 may play an important role in colon cancer progression and could serve as a prognostic biomarker to identify patients at risk of developing metastasis or recurrence after colonectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
84
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 27 publications
8
84
1
2
Order By: Relevance
“…10,25 Specifically, increased protein expression of IGF2BP3 has been associated with enhanced tumor aggressiveness, metastatic behavior and inferior outcome of various solid cancers. [12][13][14][15][16][17][18] Recently, there has been growing interest in the IGF pathway from a therapeutic perspective, as monoclonal antibodies and small molecules targeting the IGF1 receptor have become available a few years ago and initial, small phase I and II, trials showed encouraging results in individual patients. 25 In this study, we investigated the mRNA expression levels of several molecules involved in IFG signaling in mantle cell lymphoma cell lines and primary mantle cell lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,25 Specifically, increased protein expression of IGF2BP3 has been associated with enhanced tumor aggressiveness, metastatic behavior and inferior outcome of various solid cancers. [12][13][14][15][16][17][18] Recently, there has been growing interest in the IGF pathway from a therapeutic perspective, as monoclonal antibodies and small molecules targeting the IGF1 receptor have become available a few years ago and initial, small phase I and II, trials showed encouraging results in individual patients. 25 In this study, we investigated the mRNA expression levels of several molecules involved in IFG signaling in mantle cell lymphoma cell lines and primary mantle cell lymphoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, IGF2BP3 was found to be overexpressed in pancreatic cancer. 11 More recently, increased IGF2BP3 protein expression has been reported in a variety of solid tumors and was found to be associated with a higher histological grade, 12 progression or metastasis 13,14 and with an unfavorable outcome. [15][16][17][18] These data indicate that IGF2BP3 may promote tumor cell proliferation and progression by enhancing signaling via the IGF pathway.…”
mentioning
confidence: 99%
“…It has been reported that IGF2BP3 is a prognostic and diagnostic biomarker in many tumoral tissues including colorectal adenocarcinoma (22)(23)(24)(25). We stained 112 formalin fixed paraffin embedded colorectal tumor tissues (NOS type) with an immunohistochemistry method and showed that 50% of these tumors were cytoplasmically positive for IMP3.…”
Section: Discussionmentioning
confidence: 97%
“…It is postulated that IMP3 is expressed at low or undetectable levels in mature tissues, except for the placenta (8). However, the expression of IMP3 was reported in tumors of many organs such as the kidney (13), liver (14), endometrium (15), cervix (16), ovary (17), breast (18)(19), pancreas (20), stomach (21), colon (22), bladder (23), and lung (24), as well as in malignant melanoma (25) and some sarcomas (26)(27). Since IMP3 is detected in fetal and neonatal tissues and various tumors, it is considered an oncofetal protein.…”
mentioning
confidence: 99%